2015
DOI: 10.1155/2015/467498
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors for Cancer Prevention Behaviors in Workplace Using Protection Motivation Theory

Abstract: Backgrounds. The aim of this study was to describe the preventive behaviors of industrial workers and factors influencing occupational cancer prevention behaviors using protection motivation theory. Methods. A self-administered questionnaire was completed by 161 petrochemical workers in Iran in 2014 which consisted of three sections: background information, protection motivation theory measures, and occupational cancers preventive behaviors. Results. A statistically significant positive correlation was found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 28 publications
14
42
1
1
Order By: Relevance
“…The results of Morowati Sharifabad et al 's study[27] and Tazval et al 's study[28] are consistent with the results of this study. Their finding suggested that as education increases, PHS increases as well.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of Morowati Sharifabad et al 's study[27] and Tazval et al 's study[28] are consistent with the results of this study. Their finding suggested that as education increases, PHS increases as well.…”
Section: Discussionsupporting
confidence: 92%
“…The results of several studies are consistent with the results of this study. [2732] The positive correlation suggests that a person with a higher self-efficacy can act consistently (e.g. not smoke hookah) against a health risk (hookah), and this can reduce health risks, protect his health, and prevent the consequences of inappropriate behavior (hookah smoking).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Zare-sakhvidi et al and Rahaei et al have obtained the similar results. However, self-efficacy was a more powerful predictor than response efficacy in Zare-sakhvidi et al study [11,13]. Self-efficacy, more over PMT, has been applied in other health behavior models including health belief model [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Those who knew behaviors such as using sunscreen, cap, sunglasses, wearing sun-blocking clothes as efficient and effective, had more powerful intention to apply these behaviors. Studies by Zare-sakhvidi et al and Rahaei et al have indicated that this construct is one of the powerful predictors of protection motivation against cancers in adults (11,13).…”
Section: Discussionmentioning
confidence: 99%